Flavonoids, gut microbiota and cardiovascular disease: Dynamics and interplay - Hadi Mansour (17821430) (2024)
Cardiovascular disease (CVD) remains the leading cause of global morbidity and mortality. Extensive efforts have been invested to explicate mechanisms implicated in the onset and progression of CVD. Besides the usual suspects as risk factors (obesity, diabetes, and others), the gut microbiome has emerged as a prominent and essential factor in the pathogenesis of CVD. With its endocrine-like effects, the microbiome modulates many physiologic processes. As such, it is not surprising that dysbiosis-by generating metabolites, inciting inflammation, and altering secondary bile acid signaling- could predispose to or aggravate CVD. Nevertheless, various natural and synthetic compounds have been shown to modulate the microbiome. Prime among these molecules are flavonoids, which are natural polyphenols mainly present in fruits and vegetables. Accumulating evidence supports the potential of flavonoids in attenuating the development of CVD. The ascribed mechanisms of these compounds appear to involve mitigation of inflammation, alteration of the microbiome composition, enhancement of barrier integrity, induction of reverse cholesterol transport, and activation of farnesoid X receptor signaling. In this review, we critically appraise the methods by which the gut microbiome, despite being essential to the human body, predisposes to CVD. Moreover, we dissect the mechanisms and pathways underlying the cardioprotective effects of flavonoids. Other Information Published in: Pharmacological Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.phrs.2024.107452